The Invisible Enemy - Eni-Olorunda, Tolu (Macmillan Nigeria Publishers Ltd, 2006)
Mary Spencer comes to the city from Magogo village with the ambition of becoming a medical doctor.Uncle Bato is determined to help her if she learns to live like a city girl.
Keywords: City Life; Juvenile Fiction; Realistic